Exploring the Narratives and Agency of Children with Migrant Backgrounds Within Schools : Researching Hybrid Integration. - Baraldi, Claudio. (Migration and Education Series, 2023)
This edited volume presents the results of a European research project - 'CHILD-UP' (Children Hybrid Integration: Learning Dialogue as a way of Upgrading Policies of Participation), which supports the hybrid integration of children with migration backgrounds into schools across Europe.